Shantytown protest in Pinochet's Chile - Schneider, Cathy Lisa, 1955- (Temple University Press, 1995)
"A study of local-level social and political organizations during the early years of military rule and of the protest between 1983-86. The author points to the presence (or absence) of a strong Communist party nucleus and a historical tradition (pre-1973) of political involvement, not levels of poverty or unemployment, as factors determining the extent of politicization and involvement. She offers more detailed portraits of activists and organizations than Oxhorn, but less coverage of their relations with political parties, and of developments beyond 1986"--Handbook of Latin American Studies, v. 57.